Understanding the clinical characteristics of lesbian, gay, and bisexual military service members and adult beneficiaries within an inpatient psychiatric sample. Issue 2 (10th December 2021) - Thompson, Matthew F.; Luk, Jeremy W.; LaCroix, Jessica M.; Perera, Kanchana U.; Goldston, David B.; Weaver, Jennifer J.; Soumoff, Alyssa; Ghahramanlou‐Holloway, Marjan
Abstract: Background: Limited knowledge exists regarding targets for suicide‐focused care among high‐risk United States (U.S.) civilian and military sexual minorities. Purpose: This study aimed to understand the demographic and clinical characteristics of a suicidal sexual minority sample, psychiatrically hospitalized in military treatment facilities, to advance future targeted care for this vulnerable subgroup. Methods: Secondary analysis of baseline data from a multisite psychotherapy randomized controlled trial was performed comparing those who self‐identified as lesbian, gay, or bisexual (LGB; n = 39) to heterosexual participants ( n = 170). Results: LGB participants were more likely than heterosexual participants to be younger, female, never married, and enlisted rank. LGB participants reported significantly lower family support, higher perceived burdensomeness, lower acquired capability for suicide, and were twice as likely to report that they could not control their suicidal thoughts. LGB and heterosexual participants reported similar levels of other suicide risk indicators and similar lifetime suicidal ideation and attempt histories. Conclusions: Compared to heterosexual participants, LGB participants reported increased risk indicators for suicide yet similar lifetime suicidal ideation and attempt histories. Suicide prevention programs should address the unique needs of this vulnerable subgroup. Interventions targeting family support, perceived burdensomeness, and controllability of suicidal thoughts may be promising.